Community perceptions of maternal health services in rural areas in Dedza district in Malawi - Divala, Priscilla (My University, 2020)
Background: Maternal health services continue to be a challenge in rural areas of Malawi. Understanding this challenge, in the Malawian context, is important in achieving a responsive health system. Maternal health care services are more effective if communities perceive them as reliable and also if there is a shared understanding between the community and the health-care providers. Aim: This study aimed to explore community perceptions of maternal health services in rural areas of Dedza District in Malawi. Methods: This study employed exploratory qualitative research design. For data collection, three focus group discussions (FGDs) and 15 one-on-one in-depth interviews were conducted. In total, 24 men participated in the FGDs and the 15 one-on-one interviews were conducted on women.Data was collected using Chichewa, a native Malawi language, and were translated to English. Back translation was performed for credibility purposes. Inductive coding of participants’ quotations was utilized for thematic analysis. Themes were generated by comparing codes from the in-depth interviews and those from the FGDs. MAXQDA software, version 12, was used both for management and analysis of data. Results: Five themes could be generated from the community’s perceptions on maternal health service provision. The first three themes report on the available services and users’ appreciation of those services. The themes are; 1) Maternal health services package understanding; 2) Community appreciation and preference of health care providers 3) Maternal health services provision barriers and challenges. Themes 4 and 5 expose challenges that are faced by the health system. Respectively, these themes are; 4) iv Maternal health sercive patient challenges; 5) Proposals on maternal health service improvement plans. Conclusion: In Malawi’s rural areas there are available maternal health services. Some of these are appreciated by the users. However, there are challenges that both the health system and respective users face. In order to reduce maternal mortality rate in Malawi’s rural areas, it is paramount for people, especially those that are poor, to utilize maternal health services. Access to health services was improved through the introduction of community by-laws. This has since decreased maternal mortality rate in Malawi. However, the ethical implications of the introduction of community by-laws compromise women’s autonomy in health care decision making.
A research report submitted in partial fulfilment of the requirements for the degree of Master of Public Health (Rural Health) to the Faculty of Health Sciences, University of the Witwatersrand, Johannesburg, 2020